Política Monetária e a Agricultura Em Moçambique - Abbas, Máriam (Observatório do Meio Rural, 2015)
Este estudo pretende verificar a causalidade de curto e longo prazo entre a política monetária e a produção agrícola em Moçambique. Para esse efeito estudar-se-ão variáveis como taxas de juros, oferta monetária, inflação, taxa de câmbio e crédito agrícola.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura

Ex-Post Project Evaluation 2014 (Mozambique, Bhutan, Palestine) - JICA (Japan International Cooperation Agency (JICA), 2015)
The project’s objective was to improve access to lower secondary education, by constructing 4 schools and extending the capacity of existing schools and their facilities in the target areas of Maputo Province and Gaza Province, thereby contributing to improvement of the quality of education. The project’s objective coincides with the development policy of Mozambique, which emphasizes the expansion of access to secondary education at the time of planning and also ex-post evaluation. It also coincides with the development needs of Mozambique, because there are very strong needs for the construction of secondary schools in order to respond to the rapid increase in the number of students who wish to receive secondary education. It was also relevant to Japan’s ODA policy at the time of planning. Thus, its relevance is high. The project cost and the project period are the same as planned, thus its efficiency is high. As to the effects of the project, 4 schools and 58 classrooms were constructed as planned, the number of students enrolled at those schools exceeded the original target, and other positive effects were revealed in terms of the access to secondary education such as improvement of educational environment and reduction in commuting time to schools. Thus, its effectiveness is high. There were some negative impacts of the project; for example, the IT classrooms of some schools were not utilized as planned, and the promotion rate declined in some grades of 2 schools in Maputo Province partly because the number of students per classroom far exceeded the capacity of the classroom. On the other hand, there were some positive indirect impacts as planned; the promotion rate improved in 2 schools in Gaza Province, and the learning attitudes of students and teaching attitudes of teachers also improved. Thus, the project’s effectiveness and impact are high. As to the aspects of operation and maintenance (O&M), there were no serious problems in the technical aspect, but there were some problems in the institutional and financial aspects, as well as the O&M situations. Thus, sustainability of the project is fair. In the light of the above, this project is evaluated to be highly satisfactory.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; development partners / parceiros de cooperação; education / educação

EU & Partners' Country Roadmap for Engagement with Civil Society: 2016-2019 - Government of Canada; Government of Switzerland; UNICEF; USAID (Governments of Canada, Switzerland, UNICEF, USAID, 2015)
Study commissioned by EU and other countries on CSO engagement. The identification of priorities is based on four criteria: • The findings of the recent mapping of civil society in Mozambique commissioned by the EU and other studies; • The official EU guidance on the preparation of a civil society roadmap; • Existing and planned EU interventions and of the partners engaged in the roadmap; • The need to combine a longer term perspective with concrete actions over the next 3 years. The priorities constitute primarily a common agenda that will shape and orient discussions and collaboration between the roadmap partners. It allows situating individual interventions in a broader collective framework and as such adds a strategic dimension to programming.
Keywords: #Policy Document / Documento de Política; G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação

Relatório do Estudo sobre a Sustentabilidade das Organizações da Sociedade Civil (versão final) - Eurosis (Eurosis, 2015)
O presente documento constitui o Relatório do Estudo de Sustentabilidade das Organizações da Sociedade Civil solicitado por 5 Organizações Não Governamentais (DIAKONIA, FHI360, HELVETAS, KEPA e OXFAM NOVIB) e realizado pela EUROSIS Consultoria e Formação em Gestão. De forma sintetizada, este estudo tinha como objectivos chave: a) mapear o entendimento que a governação e gestão das OSC têm sobre sustentabilidade e seus desafios; b) ajudar a desconstruir a percepção que limita a sustentabilidade à viabilidade económico-financeira das OSC, trazendo à superfície outras dimensões também relevantes para o efeito; c) recomendar acções para a tomada de decisão dos diversos actores que trabalham no fortalecimento das OSC. Tendo em consideração os seus objectivos, este estudo está estruturado em quatro componentes chave: • revisão de literatura internacional para identificação de factores que, de acordo com pesquisa internacional, influenciam sustentabilidade de OSC. • recolha de dados (através de questionários auto-administrados, entrevistas face-a-face e workshops) para o levantamento de percepções e opiniões de OSC com relação ao conceito de sustentabilidade, limitantes colocadas pelo contexto moçambicano à sustentabilidade de OSC, fragilidades das próprias OSC que não ajudam à sustentabilidade). Importa referenciar que para a recolha de dados: 79 representantes de 62 OSC preencheram o questionário online; foram realizadas 19 entrevistas semiestruturadas e em profundidade; e foram realizados três workshops em Maputo, Chimoio e Nampula com a participação de 69 representantes de 54 OSC. • análise e conclusões que incluiu: a) comparação dos factores mencionados em literatura internacional com os mencionados pelos respondentes no estudo para identificação de factores comuns e identificação daqueles que não parecem estar no campo das preocupações ou prioridades da maior parte das OSC respondentes; b) tendo em consideração a comparação anterior, elaboração de proposições sobre os factores que, na nossa opinião, afectam ou limitam a sustentabilidade de OSC em Moçambique. • recomendações elaboradas com base na análise e nas conclusões apresentadas
Keywords: *non-public; G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil

PEDEC-NACALA Final Study Report Analysis Report: Strategic Master Plan on Strengthening of Nacala Corridor Region-Wide Freight Network for Agricultural and Mining Sectors - Oriental Consultants Global Co., Ltd.; RECS International Inc.; International Development Center of Japan Kokusai Kogyo Co., Ltd. (Japan International Cooperation Agency (JICA), 2015)
This document was prepared as an analysis report for sharing a study result on a particular theme as part of ‘The Project for Nacala Corridor Economic Development Strategies (PEDEC-Nacala)’ which is a technical assistance project supported by Japan International Cooperation Agency (JICA) for the Government of Mozambique. PEDEC-Nacala formulated integrated development strategies for corridor development by an integrated approach involving several sectors and also by giving consideration to environmental and social aspects. The actual strategies formulated in PEDEC-Nacala and details of the present situation of the Nacala Corridor Region are compiled into the PEDEC-Nacala Final Study Report
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura

Estratégia da Suécia para a cooperação para o desenvolvimento com Moçambique, 2015-2020 - Ministry for Foreign Affairs - Sweden (Ministry for Foreign Affairs - Sweden, 2015)
Within the framework of this strategy, Swedish development cooperation with Mozambique aims to make use of the increased interest and potential to utilise the country's natural resources in a socially, economically and environmentally sustainable way. It also aims to improve opportunities for people living in poverty to contribute to and benefit from economic and democratic development. The strategy is valid for the period 2015–2020 and comprises a total of SEK 4.1 billion.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; natural resources / recursos naturais

Strategy for Sweden’s development cooperation with Mozambique, 2015–2020 - Ministry for Foreign Affairs - Sweden (Ministry for Foreign Affairs - Sweden, 2015)
Within the framework of this strategy, Swedish development cooperation with Mozambique aims to make use of the increased interest and potential to utilise the country's natural resources in a socially, economically and environmentally sustainable way. It also aims to improve opportunities for people living in poverty to contribute to and benefit from economic and democratic development. The strategy is valid for the period 2015–2020 and comprises a total of SEK 4.1 billion.
Keywords: G - Mozambique / Moçambique; L - english / inglês; economic development / desenvolvimento económico; natural resources / recursos naturais

Business licensing: a key to investment climate reform - Ing, Lili Yan; Magiera, Stephen; Widiana, Anika (ERIA, 2015)
Reforming business licensing is a key starting point for improving the investment climate. Complex licensing procedures may encourage firms to remain unregistered, giving rise to difficulties later in accessing finance from formal financial institutions and constraining productivity and expansion. Across sectors, this can suppress the establishment of new firms and therefore the creation of new jobs, dragging down overall economic growth. Improving and reforming business licensing can significantly increase the number of businesses and thus help nurture employment creation. Several quick-win interventions are possible. First, there is a need to improve the quality of the business licensing website and help desk. The website and help desk should act as a frontline in dealing with investment regulations and policies for investors. Improvements should cover both hard and soft infrastructure of the website and help desk, including the skills of officials. Second, business license simplification should be continued by limiting licenses to those that serve their objective and cutting unnecessary licenses, and or consolidating licenses. Third, full implementation of electronic application and payment systems for business licenses should be fostered, together with increasing the nonfiscal incentives for firms to become registered. The registration system should also function as a nationwide database which could then be a source of reliable information both on firms and for firms, linked to government programs and grants, and business regulation updates. Fourth, a transparent system to show the progress of each business application should be set up, together with a recorded evaluation system in which users can provide feedback to improve the system. Finally, efforts in the medium term should focus on improving coordination among government agencies and clarifying the roles of central and local regulations, both horizontally and vertically.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

Accountability Through Active Citizenship: Improving Petroleum Governance in Ghana, Mozambique & Tanzania - Arregui, Chiqui (Oxfam America, 2015)
The objective of the baseline survey is to analyze and document the situation around accountability, transparency and governance of the O&G sector in the country prior to the implementation of the Oxfam project. It focuses on a selected group of indicators chosen for the country program logical framework, identified and approved in the Baseline Inception Phase. A total of 33 people were interviewed in the context of this baseline. This was accompanied by a thorough national and international literature review. It was not possible to gain access to some key Government and CSO representatives at sub-national level and any of the three O&G companies contemplated in the context of this baseline, which could affect the comprehensiveness of findings. It is expected that a similar exercise be conducted at the end of the program to gauge the changes brought about by program interventions. The fieldwork for the baseline was conducted in December 2014. Baseline findings are presented in line with program outcomes, broadly focusing on building the capacities of (i) communities (Outcome 1); (ii) CSOs and the media (Outcome 2) and (iii) Other stakeholders (Outcome 3).
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; governance / governação

A Macroeconomia e a Produção Agrícola em Moçambique - Abbas, Máriam (Observatório do Meio Rural, 2015)
Este trabalho procura verificar a relação entre variáveis macroeconómicas e a produção agrícola em Moçambique. O sector agrícola desempenha um papel fundamental no desenvolvimento da economia moçambicana. Assim sendo, torna-se importante compreender a relação entre o ambiente macroeconómico e o sector. De acordo com Ali et al. (2010) a economia agrícola mundial tem sido substancialmente sensível aos movimentos dos indicadores macroeconómicos. Vários investigadores e economistas concordam que as alterações na política macroeconómica têm, muitas vezes, um impacto significativo na economia agrícola. Sendo assim, o sector agrícola não deve ser tratado como um sector fechado às alterações estruturais no ambiente macroeconómico e à integração dramática nos mercados internacionais, Schuh (1976) em Letsoalo e Kirsten (2003).
Keywords: G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; economic development / desenvolvimento económico

Revoltas da fome: protestos populares em Moçambique (2008-2012) - Brito, Luís de; Chaimite, Egídio; Pereira, Crescêncio; Posse, Lúcio; Sambo, Michael; Shankland, Alex (Cadernos IESE, 2015)
Em Fevereiro de 2008 e Setembro de 2010, as cidades de Maputo e Matola foram palco de protestos violentos contra a subida do custo de vida, protagonizados por grupos de populares. Tais protestos foram logo depois replicados em algumas outras cidades do país, mas numa dimensão bem mais restrita e rapidamente controlados pelas forças policiais. Em Novembro de 2012, um novo protesto se desenhou, mas a acção repressiva imediata nos locais críticos de concentração dos populares pelas forças da polícia, que nos últimos anos tinha sido reforçada fortemente em homens e material, impediu que a violência se generalizasse, ainda que não tenha evitado a paralisia quase total da actividade no grande Maputo durante um dia e meio. Neste relatório procuramos mostrar que, se estas revoltas se enquadram num movimento mais amplo que desde 2008 tem abalado muitos países em consequência do aumento e da alta volatilidade dos preços alimentares no mercado internacional, elas exprimem sobretudo dinâmicas económicas locais e são um resultado da exclusão social e política a que são votadas as camadas sociais urbanas mais pobres em Moçambique. O relatório começa por apresentar uma breve perspectiva histórica e caracterização da natureza da economia moçambicana e da tradição política autoritária que tem sido dominante desde a proclamação da independência, ainda que coexistindo com uma profunda mudança nas alianças políticas do partido no poder, para depois abordar a questão alimentar e do custo de vida, assim como o contexto imediato dos protestos, os discursos e representações sobre os mesmos e o tipo de resposta por parte do governo.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social

An Analysis of Mozambique’s Political and Economic Networks - Chivangue, Andes; Cortez, Edson (CEsA - research center part of CSG/Research in Social Sciences and Management, 2015)
This paper analyses the social networks existing among politicians and economists in contemporary Mozambique, using the SNA-Social Networks Analysis method to identify the links between these individuals, to discern their relationships and to measure both the density and the centrality of the political-business network. Mozambique’s political and business elite is thus identified. A network sociogram is presented identifying the individual position in the network and the linkages among these individuals and several positional metrics of the individuals in the network are estimated, allowing identifying each individual and its influence in the network. As this network is resource accumulation driven, this exercise permits to identify the main political and economic individual active in Mozambique economy. President Guebuza define the major network centre and other individuals, Joaquim Chissano, the former president, and Graça Machel, the widow of another former president. Policy implications are derived and the links between them displayed, allowing for an accurate view of Mozambique’s political and business world.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

N’weti’s Community Scorecard Experience in Nampula: a Case Study - Franco, Erika Lopez; Dumangane, Sansão (Institute of Development Studies and N'weti, 2015)
This case study was commissioned by N’weti Comunicação para a Saúde to explore the changes emerging from the implementation of an adapted version of the Community Scorecard (CSC) tool in 11 health facilities catchment areas in Nampula. This case study discusses how N’weti has adapted the Community Scorecard (CSC) tool to better improve the quality of the participation and prospects of accountability for citizens. The case study presents evidence that the adapted CSC tool has resulted in an increased awareness of rights, an improved relationship with the service providers, a revitalisation of the health unit Co-management Committees, citizens feeling that their voice is being heard, and N’weti is recognised by people and authorities as catalyser and legitimate mediator of this voice. However, challenges also surfaced which N’weti must reflect and learn from. The first relates to the meaningful control from regular citizens (rather than NGO staff members) of the institutionalisation, follow-up of commitments and advocacy actions derived from the implementation of a CSC process. Other challenges refer to social exclusion, the lack of a deeper understanding of power dynamics, and the fact that ignoring previous histories of citizen engagement and other contextual factors can be misleading as not all change can be directly attributed to the implementation of the CSC.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Meconta; GD - Moma; GD - Rapale; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Gás para desenvolvimento ou apenas dinheiro? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
O gás de Moçambique pode ser usado para promover industrialização e desenvolvimento rural desde que, a partir de agora, sejam feitas as opções correctas. As actuais prioridades vão para os megaprojectos baseados na exportação, que prometem altos rendimentos mas que, tal como os megaprojectos anteriores, fazem pouco pela criação de empregos ou pela redução da pobreza. Os megaprojectos custando dezenas de bilhões de dólares são essenciais, mas o Conselho de Ministros pode orientar as negociações de maneira a darem a prioridade mais alta à utilização do gás para criar uma indústria nacional e empregos, mesmo que reduza as receitas a curto prazo
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Gas for development or just for money? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
Mozambique’s gas can be used to promote industrialisation and rural development, but only if key choices are made now. Current priorities are for export based mega-projects promising high revenues, but like past mega-projects doing little to create jobs or reduce poverty. Mega-projects costing tens of billions of dollars are essential, but the Council of Ministers can instruct that negotiations give a higher priority to using the gas to create a domestic industry and jobs, even if it reduces short term income.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Child Marriage and Adolescent Pregnancy in Mozambique: Policy Brief - Hodges, Anthony (UNFPA, Meninas e Não Noivas, UNICEF, 2015)
Child marriage is one of Mozambique’s most serious but largely ignored development challenges – requiring far greater attention from policy makers Child marriage rates are still very high despite a long-term decline, especially in marriage before the age of 15. Economic pressures and the incentive of bride price appear to be powerful factors driving parents to marry off their daughters at a young age. The high rates of child marriage cannot be allowed to continue without a vigorous response from the government, civil society and development partners.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Mapping study of Civil Society Organisations in Mozambique - Topsøe-Jensen, Bente; Pisco, Alice; Salimo, Padil; Lameiras, João (ALTAIR Asesores and Agriconsulting. S.L, 2015)
The Mapping Study of Civil Society Organizations (CSOs) in Mozambique was carried out during the first half of 2015, within the context of preparation for the Roadmap of the European Union (EU), Member States and other partners for engagement with civil society. Data collection included document analysis, and interviews with CSOs, international partners and Mozambican government institutions at national, provincial, district and local level. In the first phase of the field work, nine provincial workshops were held, and in the second phase four workshops were held for verification of findings and validation of recommendations. The overall objective of the mapping study is to provide the EU and all interested parties with a comprehensive overview of the state of CSOs in Mozambique, including identification of their needs and proposals for maximizing their influence in the definition and monitoring of public policies. The study also presents recommendations on the priorities to include in the EU Roadmap for engagement with civil society, and may thus contribute to improving the strategy for support to CSOs within current programming. The specific objectives are to: - Analyse the global state of play of the civil society in Mozambique, particularly regarding the environment, structure, capacity, engagement and sustainability of its organizations; - Identify existing the gaps, the fundamental needs and the opportunities for the CSOs to get involved in and influence policy processes, to monitor implementation of state commitments, and in general to claim transparency in public processes and good governance; - Provide specific recommendations on how to better meet needs identified by suggesting priorities and actions for programmes and other civil society support interventions.
Keywords: G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil

The land grabbers of the Nacala Corridor: A new era of struggle against colonial plantations in Northern Mozambique - UNAC; GRAIN (UNAC and GRAIN, 2015)
This report looks at the companies already setting up agribusiness operations in the Nacala Corridor, an area that the government has prioritised for agribusiness development. These companies, typically structured through offshore tax havens and often connected to Mozambican political elites, have been grabbing lands and extracting wealth in ways reminiscent of the country's colonial days.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura